IMPROVING METHODS FOR DEVELOPING STUDENTS’ CREATIVE SKILLS THROUGH EXTRACURRICULAR ACTIVITIES (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article analyzes, from a scientific and pedagogical perspective, the issues of improving methods for developing students’ creative skills through extracurricular activities. In the modern education system, the development of students’ creative thinking, independent decision-making abilities, creative approaches to problem-solving, and communicative competencies is considered one of the most pressing pedagogical tasks. From this perspective, the article highlights the didactic potential of extracurricular activities, their pedagogical essence, and their role in fostering students’ creativity. During the study, the effectiveness of interactive methods, particularly the “Graphic Test” and “Find the Mistake” methods, as well as STEAM-based activities, was analyzed. The results of the experimental work demonstrated that extracurricular activities significantly contribute to the development of students’ creative thinking, independent learning, and problem-solving skills. Based on the research findings, practical recommendations for improving extracurricular activity methodology were developed.